Understanding Nonresponse Rates : Insights from 600,000 Opinion Surveys - Reyes, Germán (Published by Oxford University Press on behalf of the World Bank, 2021)
Despite the central role of surveys in empirical research, academics have not paid enough attention to the factors that affect response rates. This is especially concerning since survey response rates—of both household and opinion surveys—have been declining over time (Meyer, Mok, and Sullivan, 2015), which might lead to distorted survey results. This paper explores how the underlying design of each survey—such as its length and the day of the week in which the survey was conducted—affects the response rates of the survey.